Control of atropoisomerism: an access to valuable compounds - Choppin, Sabine; Wencel-Delord, Joanna; Colobert, Françoise (Comptes Rendus. Chimie)
Many natural, biologically active compounds are stereogenic with a unique tridimensional structure that is on the origin of the specific interactions with the active binding site.This concept of chirality goes beyond chiral stereocenters, englobing also atropoisomerism related to a hindered rotation around an axis with the isolation of atropostable conformers at room temperature. Atropoisomerism is well-known in biaryls, however this phenomenon is encountered in many pharmaceutically relevant compounds such as heterobiaryl, diarylamines, benzamides and anilides.Currently four FDA-approved drugs are atropostable and many others are in clinical trials. It is also important to note that almost 30% of recent FDA-approved small molecules are “proatropisomeric” and interact with a target in a specific chiral conformation.Given this vivid interest in C–C but also C–N atropisomerically stable compounds, this account will detail the new atropoisomeric strategies we developed and their applications in the synthesis of relevant molecules and ligands.